Modeling and Analysis of Omnidirectional Wheeled Vehicles Using Velocity-based Impedance Control - N. M., Adam; Addie, Irawan (2021)
This paper presents the velocity-based impedance control that would account for the inertia forces acting on the omnidirectional wheeled vehicle duriing cornering motions. As favorable omni-vehicle, omnidirectional mecanum wheeled vehicle (OMWV) was selected as a platform in this study. Concerning the problem statements in the dynamic analyses, the control design has considered the difference in vehicle forces because the vehicle's interaction forces were indirectly controlled by the vehicle's velocities. The axial velocities control of the OMWV, vertical and horizontal axial motions on cornering periods were highlighted in this research. The simulation results show that with velocity inputs, the different forces on the OMWV axial motion of the vehicle could be reduced. Furthermore, the reduction in vehicle velocity influenced the overall kinetic energy of the system, which reduced the inertia effect.